Respuesta :

Answer:

x^9

Step-by-step explanation:

The rule of exponents that applies is ...

(a^b)^c = a^(b·c)

For your problem, you have a=x, b=(3/2), c=6, so ...

(x^(3/2))^6 = x^(3/2·6) = x^9

Answer:

[tex]x^9[/tex]

Step-by-step explanation:

We are given that an expression

[tex]\left\{(x)^{\frac{3}{2}\right\}^6[/tex]

We have to simplify the given expression

In order to simplify the expression we will use given below rule

We know that [tex](a^b)^c= a^{b\cdot c}[/tex]

Using this rule

[tex](x)^{\frac{3}{2}\cdot 6}[/tex]

[tex](x)^{3\cdot 3}[/tex]

[tex]x^9[/tex]

[tex]\left\{(x)^{\frac{3}{2}\right\}^6=x^9[/tex]